Implementation of Improvement Agribusiness Strategy Model of Cacao, Technology Capability To Control Vascular Streak Dieback (VSD), Motivation To Increase Productivity and Value of Product (Farmer Focus On Export Market Orientation at Cacao Center In Sula - Rosida P. Adam (Syntax Literate, 2022)
The purpose of this study is the implementation of agribusiness strategy model of cacao to solve the low productivity caused by Vascular Streak Dieback (VSD) in Indonesia, specifically in Sulawesi. Furthermore, in export level it is still in primary product and not have processed, which resulted low competitiveness product. Qualitative and quantitative analysis were used as an analytical method, while the implementation model was used to introduce Trichoderma and Bokashi Plus fertilizer to farmer. The result showed that the implementation of agribusiness mode of Cacao at Central Sulawesi and West Sulawei as a sample location, five (5) sub-systems of agribusiness were not maximal to contribute, especially in sub-system agricultural production and sub-system financial. Farmer’s motivation to learning technology to control VSD by using Trichoderma and Bokhasi Plus fertilizer was high, which can be shown that they very enthusiastic to accept the technology. The effectivity of implementation agribusiness strategy model also showed a good result, though some of farmers were already land transformed to other commodity.